Tradução e adaptação transcultural do instrumento spiritual assessment scale no brasil - Freitas, Elizangela Oliveira (2013)
Spirituality is considered an integrant part of nursing care. This study aimed to perform a cross-cultural adaptation of the Spiritual Assessment Scale (SAS) to Brazil. A specific instrument for cross-cultural adaptation based on Lynn's studies (Likert scale) was developed. The first step consisted in the application of the instrument developed by the authors to assess the SAS by 6 experts in the area of Spirituality and Nursing and with 11 patients from the clinical medical unit to review the SAS instrument with 21 questions. After conducting statistical tests, the questions were considered appropriate for use in the research as demonstrated by Cronbach's alpha, which indicated an acceptable reliability of the instrument. It can be stated that in both groups (experts and patients) internal consistency was high, the characteristics of the original scale were preserved even after the stages of translation and adaptation to Brazil.